Questions for the Adult Educator on a Virtual Odyssey: An Analysis of Internet and Web-based Learning - Sue Webb (Adult Education Research Conference, 2000)
This paper examines the argument that lifelong learning should become increasingly dependent on education technology because this will alleviate many of the barriers to learning adults face. Lifelong learning is diverse, and so caution is needed when generalising from case specific research. The premise that new learning technologies promote social inclusion is still relatively untested.